2020
DOI: 10.1080/08998280.2020.1735238
|View full text |Cite
|
Sign up to set email alerts
|

Zieve syndrome in acute alcoholic hepatitis

Abstract: A 31-year-old woman presented with acute alcoholic hepatitis, jaundice, anemia, and hypertriglyceridemia following ethylene glycol poisoning. She had no previous history of anemia or gastrointestinal bleeding. Laboratory findings were consistent with acute hemolytic anemia. She was diagnosed with Zieve syndrome and was managed with supportive measures. Zieve syndrome is a rare occurrence with only a handful of published case reports. Although rare, the diagnosis should be on the differential in this subgroup o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…It is characterized by the triad of Coombs-negative hemolytic anemia, cholestatic jaundice, and transient hyperlipidemia in patients with a history of alcohol abuse and liver disease [ 1 ]. The mechanism of hemolysis is unclear, but it has been related to an accumulation of polyunsaturated fatty acid and cholesterol inside RBC membranes [ 3 , 4 ]. These changes cause severe hyperbilirubinemia in ZS due to several factors, including hepatocellular damage and hemolysis [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is characterized by the triad of Coombs-negative hemolytic anemia, cholestatic jaundice, and transient hyperlipidemia in patients with a history of alcohol abuse and liver disease [ 1 ]. The mechanism of hemolysis is unclear, but it has been related to an accumulation of polyunsaturated fatty acid and cholesterol inside RBC membranes [ 3 , 4 ]. These changes cause severe hyperbilirubinemia in ZS due to several factors, including hepatocellular damage and hemolysis [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the associated severe hemolysis seen in ZS can be inappropriately used to overestimate morbidity and mortality when calculating MDF, based on the abnormally high TB level, without considering other etiologies [ 6 , 7 ]. However, it has also been reported that patients with a deficiency of lipoprotein lipase can be predisposed to transient hyperlipidemia in more than 50% of patients with ZS [ 3 ]. MDF is an excellent evidence-based tool to assist in risk stratification among patients with alcoholic hepatitis; it improves outcomes based on the disease severity and helps establish the use of specific interventions [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our patient’s diagnosis of Zieve syndrome was established based on the presence of profound jaundice, hemolytic anemia, an alcohol use disorder, and characteristic peripheral blood smear findings of acanthocytes and schistocytes [ 8 ]. Although transient hyperlipidemia is considered a classic finding in Zieve syndrome, lipid levels can be normal on presentation in up to half of patients, as detection and diagnosis can occur months after the initial massive mobilization of fat [ 8 ]. Our patient had little medical care prior to this hospitalization.…”
Section: Discussionmentioning
confidence: 99%